Arum palaestinum delays hepatocellular carcinoma proliferation through the PI3K-AKT-mTOR signaling pathway and exhibits anticoagulant effects with antimicrobial properties - Dwikat, Majdi; Amer, Johnny; Jaradat, Nidal; Salhab, Ahmad; Rahim, Ahmad Abdal; Qadi, Mohammad; Aref, Aseel; Ghanim, Mustafa; Murad, Haya; Modallal, Ali; Shalabni, Kawkab (Frontiers in Pharmacology, 2023)
Abstract Arum palaestinum Boiss. (AP) is one of the wild Palestinian plants which leaves have a long history as food and medicine. The current study aimed to evaluate biological characteristics of AP extract flowers through their effects as antimicrobial, coagulation cascade activities, and anticancer molecular pathways. The aqueous extract of AP flowers were assessed for its antimicrobial activity using microdilution assay against eight pathogens, its Coaglation properties through testing prothrombin time, activated partial thromboplastin time, and thrombin time tests, and its anticancer activity through its effects on hepatocellular carcinoma The results revealed that the aqueous extract of AP has a potent antibacterial effects against P. vulgaris and E. faecium compared to ampicillin with MIC values of 6.25, 6.25 and 18 mg/ml, respectively. Moreover AP aqueous extract exert anticoagulant activity with significant prolonged results in aPTT and TT tests with both concentrations of 25 mg/ml and 50 mg/ml. The anticancer results indicate a delay in cell cycle through decreased the cell proliferation rate, delay in the S phase, and accelerate the G2-M phase with methanolic extract suggesting that (AF) flower extracts have anti-cancer properties. Moreover the Aqueous extract of AP reduced secretions of HCC αFP (P=0.0008, and decreased in both HbsAg an CFSE proliferations, in addition to shifted cells from necrosis to apoptosis of 50% and 70% in the 50 and 100 µg/ml, respectively (P<0.05). Data showed bioactive components through treatment of infectious diseases and blood coagulation disorders while could be a potential therapeutic approach for delaying HCC tumorgencity.